2020
DOI: 10.1371/journal.pntd.0008253
|View full text |Cite
|
Sign up to set email alerts
|

Role of asymptomatic and symptomatic humans as reservoirs of visceral leishmaniasis in a Mediterranean context

Abstract: Background In the Mediterranean basin, Leishmania infantum is the causative agent of visceral leishmaniasis (VL), a zoonosis in which the dog is the primary domestic reservoir, although wildlife may have a leading role in the sylvatic cycle of the disease in some areas. Infections without disease are very frequent. There is limited information regarding the role that VL patients and asymptomatic infected individuals could be playing in the transmission of L. infantum. Xenodiagnosis of leishmaniasis has been us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 34 publications
(62 reference statements)
0
38
0
1
Order By: Relevance
“…This raises the spectre that introduction of L. infantum (possibly by asymptomatic, previously deployed U.S. military servicemembers, or infected hunting and companion dogs) could lead to vector borne transmission of VL within the U.S. To better understand the risk that persons with AVL may pose with regard to anthroponotic spread, several studies have been performed within endemic countries using xenodiagnosis. Molina et al in the wake of the aforementioned Madrid outbreak identified four groups of persons with current or previous VL: asymptomatic immunocompetent persons (14 with AVL, 10 with no evidence of prior VL), untreated persons with symptomatic VL, formerly symptomatic VL patients post-treatment, and three immunocompromised patients with VL (two persons with HIV, one on therapy for multiple myeloma) [ 150 ]. None of the 14 asymptomatic VL individuals were found on xenodiagnosis to transmit infection to the sand flies.…”
Section: Prevention Secondary Transmission and Us Vector-bornementioning
confidence: 99%
See 2 more Smart Citations
“…This raises the spectre that introduction of L. infantum (possibly by asymptomatic, previously deployed U.S. military servicemembers, or infected hunting and companion dogs) could lead to vector borne transmission of VL within the U.S. To better understand the risk that persons with AVL may pose with regard to anthroponotic spread, several studies have been performed within endemic countries using xenodiagnosis. Molina et al in the wake of the aforementioned Madrid outbreak identified four groups of persons with current or previous VL: asymptomatic immunocompetent persons (14 with AVL, 10 with no evidence of prior VL), untreated persons with symptomatic VL, formerly symptomatic VL patients post-treatment, and three immunocompromised patients with VL (two persons with HIV, one on therapy for multiple myeloma) [ 150 ]. None of the 14 asymptomatic VL individuals were found on xenodiagnosis to transmit infection to the sand flies.…”
Section: Prevention Secondary Transmission and Us Vector-bornementioning
confidence: 99%
“…The risk of transmission correlated with parasite burden, with transmission frequency reaching as high as 30.6% in the patient with hematologic malignancy whose parasite load was 4360/µL prior to VL treatment, and 48.6% in one of the two HIV/VL co-infected individuals (608 parasites/µL). Strikingly, this latter individual continued to have detectable parasitemia and showed anthroponotic transmission potential even while taking anti-retroviral therapy and following treatment and institution of secondary prophylaxis for his Leishmania infection [ 150 ]. Previous work in six HIV-VL infected persons showed an association between low CD4 count and infectivity to sand flies [ 151 , 152 ].…”
Section: Prevention Secondary Transmission and Us Vector-bornementioning
confidence: 99%
See 1 more Smart Citation
“…Scientists have not fully revealed how the outbreak isolates have been able to affect middle-aged people with adequate levels of immunocompetence in this outbreak, the largest human VL outbreak in Europe. The results of the present study may help guide future research on this topic (Molina et al, 2020).…”
Section: F I G U R Ementioning
confidence: 72%
“…Asymptomatic Leishmania infected individuals, despite the typically low parasite load, might contribute to maintaining the transmission cycle of Leishmania parasites in endemic regions during episodes of increased parasite load and disease relapse [ 16 , 17 ]. In Brazil, due to the high prevalence of HIV- Leishmania coinfection observed in previous studies [ 10 , 15 , 18 ], and due to the other potential implications (e.g.…”
Section: Introductionmentioning
confidence: 99%